Collection of age of acquisition ratings for over 5,000 Japanese words - Mochizuki, Masaya; Ota, Naoto (Frontiers in Language Sciences, 2025)
The age of acquisition (AoA) refers to the age at which an individual learns specific items or words. Research on word recognition has shown that items with lower AoA—those acquired earlier—can be processed more quickly and accurately. In the field of Japanese word recognition, a large-scale database that would enable mega-study approaches has not been well-established. In this study, we developed an AoA norm for over 5,000 Japanese words. A total of 1,345 adults rated the AoA of 5,736 words using a 7-point scale. These ratings demonstrated satisfactory reliability. Furthermore, when examining the correlation with lexical decision task performance, words with lower AoA showed shorter response times and higher accuracy than words with higher AoA. These findings indicate that the AoA rating database collected in this study serves as a valuable resource for research using Japanese words.